Background influencing consumer attitude towards photovoltaic technology: A case study in the Dominican Republic - Rodriguez Gómez, Arcadio Esteba; Orgaz Agüera, Francisco; Domínguez-Valerio, Cándida María (LACCEI, 2025)
The study analyzes the factors that influence consumer attitudes toward photovoltaic technology in the Dominican Republic. Through a survey of engineering students and teachers, key constructs were identified such as knowledge about the carbon footprint, environmental concern, and ethics of sustainable consumption, assessed with the PLS-SEM methodology. The results show that technical knowledge has a limited impact, while ethics and environmental concern are stronger predictors. The need for public policies, accessible education, and subsidies to overcome economic barriers and encourage technological adoption is highlighted. It is concluded that favorable attitude depends on ethical and environmental values ​​more than technical knowledge.